Inventarisasi Siput Darat di Danau Darungan, Taman Nasional Bromo Tengger Semeru 2019 - Putri Afin Nurhayati; Boni Hermawan; Galuh Ayu Chantika Dwitara (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aims to determine the diversity of land snails that have never been revealed before. The location of this research is in the forest in the Ranu Darungan Resort area of Bromo Tengger Semeru National Park. The method used in this study is the 1.5 km transect line method. Land snails are often found behind leaves, around tree roots, and around leaf litter. The results of this study obtained 20 species of land snails, each of which has different characteristics. Land snail identification is using a land snail identification book. The lack of information about land snails in the Ranu Darungan Resort area makes this research expected to be the basis for further research.